Forty years later: Updating the Fossilization Hypothesis. (22nd February 2013) - Han, ZhaoHong
<x content-type="archive" xml:space="preserve">Abstract</x> A founding concept in second language acquisition (SLA) research, fossilization has been fundamental to understanding second language (L2) development. The Fossilization Hypothesis, introduced in Selinker's seminal text (1972), has thus been one of the most influential theories, guiding a significant bulk of SLA research for four decades; 2012 marks its fortieth anniversary. This article revisits the Fossilization Hypothesis, starting with the earliest set of questions (still the most comprehensive) (Selinker & Lamendella 1978) and using them as a basis for updating the Hypothesis. The current understanding of fossilization is presented by introducing an alternative hypothesis, the Selective Fossilization Hypothesis (Han 2009) and, in the light of that alternative, reviewing a selection of fossilizable structures documented in the recent literature.